Kajian Komparatif: Kapabilitas Dinamis Dan Strategi Diferensiasi Berkelanjutan Terhadap Penciptaan Value Bisnis Di Era Transformasi Digital - Anggit Dyah Kusumastuti; Vera Siwi Astuti; Denis Fariska; Ricko Tri Bayu Aji; Danika Haris Indrafata; Ayu Zulaikha Prasetyo Putri (Jurnal Ekuilnomi, 2026)
Changes in the business landscape due to digital transformation encourage the urgency of understanding the role of dynamic capabilities (sensing, seizing, reconfiguring capabilities) and sustainable differentiation strategies in value creation. This research aims to compare these two concepts, analyze the mediating or moderating role of dynamic capabilities, and develop an effective differentiation strategy model. Through a literature study method with content analysis, this research offers novelty in the form of a comparative-integrative study that produces a strategic model for sustainable competitive advantage. The result research show that Dynamic Capabilities strengthen the effectiveness Sustainable Differentiation Strategy by increasing organizational, adaptability, innovation, and agility. The integration of these two concepts produces a strategic model capable of enhancing business value creation in the era of digital transformation